In vitro and in vivo Repair Effects of the NCF-Col-NHA Aerogel Scaffold Loaded With SOST Monoclonal Antibody and SDF-1 in Steroid-Induced Osteonecrosis - Xu, Bing; Luo, Zeyu; Wang, Duan; Huang, Zeyu; Zhou, Zongke; Wang, Haoyang (Frontiers in Bioengineering and Biotechnology, 2022)
In the current study, we synthesized nanocellulose (NCF)-collagen (Col)-nano hydroxyapatite (NHA) organic-inorganic hybrid aerogels loaded with stromal cell derived factor-1 (SDF-1) and sclerostin monoclonal antibody (SOST McAb) and investigated their ability to repair steroid-induced osteonecrosis. Rabbit bone marrow mesenchymal stem cells (BMSCs) and human vascular endothelial cells (HUVECs) were used for the in vitro study. A rabbit steroid-induced osteonecrosis model was used for the in vivo study. The best elastic modulus reached 12.95±4.77 MPa with a mean compressive property of 0.4067 ±0.084 MPa for the scaffold containing 100% mass fraction. The average pore diameter of the aerogel was 75±18 µm with a porosity of more than 90% (96.4±1.6%). The aerogel-loaded SDF-1 and SOST were released at 40–50% from the material within the initial 3 hours and maintained a stable release for more than 21 days. The in vitro study showed osteogenesis and vascularization capabilities of the scaffold. The in vivo study showed that rabbits received implantation of the scaffold with SOST McAb and SDF-1 showed the best osteogenesis of the osteonecrosis zone in the femoral head. Imaging examination revealed that most of the necrotic area of the femoral head was repaired. These results suggest that this hybrid aerogel scaffold could be used for future steroid-induced osteonecrosis repair.